Completeness of regular inductive limits - Jan Kucera; Kelly McKennon (International Journal of Mathematics and Mathematical Sciences)
Regular LB-space is fast complete but may not be quasi-complete. Regular inductive limit of a sequence of fast complete, resp. weakly quasi-complete, resp. reflexive Banach, spaces is fast complete, resp. weakly quasi-complete, resp. reflexive complete, space.